KH Ahmad Dahlan's Teachings as a Strategy for Handling Sexual Violence in Educational Environments - Rifkisyahputra; Ghufron, Anik; Rahman, Arif; Surjono, Herman Dwi (LETIGES, 2025)
This study aims to examine the application of KH Ahmad Dahlan's teachings as a strategy for dealing with sexual violence in the educational environment. The approach used in this study is a systematic literature review, which allows researchers to compile findings comprehensively based on published scientific sources. Data were collected from various academic literature, including journal articles, scientific books, and relevant documents that discuss the teachings of KH Ahmad Dahlan, Islamic values, and the issue of sexual violence in educational environments. The analysis was conducted using a descriptive-qualitative method, which emphasizes the interpretation of the concept and values of moral and spiritual education in the teachings of KH Ahmad Dahlan. The results of the study show that the teachings of KH Ahmad Dahlan, which are rooted in the principles of progressive Islam, humanitarian values, and the spirit of educational renewal, have strong relevance in responding to the issue of sexual violence in academic environments. Through an emphasis on morality, respect for human dignity, gender equality, and the importance of character building, the teachings of KH Ahmad Dahlan are used as a strategic foundation in building a more ethical, humanistic, and transformative system for preventing and handling sexual violence. This study discusses the limitations of literature that specifically targets the teachings of KH Ahmad Dahlan on the issue of sexual violence. This study discusses the limitations of literature that specifically targets the teachings of KH Ahmad Dahlan on the issue of sexual violence.